Adhesion science - Comyn, John, 1942- (Royal Society of Chemistry, Information Services, 1997)
Annotation A brief introduction to adhesives as a branch of chemical technology. Considers the basic polymer science and chemistry of adhesives now available, surface preparation, the use of primers and coupling agents, contact angles and predicting from them, stress distribution in joints, the interaction of adhesives with the environment, and other factors. Assumes some background in chemistry. Provides suggested reading rather than full references. Annotation c. by Book News, Inc., Portland, Or.
Keywords: Adhesion.; Adhesives.; elektronické knihy; electronic books